4(2c-6)=7c

Simple and best practice solution for 4(2c-6)=7c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2c-6)=7c equation:


Simplifying
4(2c + -6) = 7c

Reorder the terms:
4(-6 + 2c) = 7c
(-6 * 4 + 2c * 4) = 7c
(-24 + 8c) = 7c

Solving
-24 + 8c = 7c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-7c' to each side of the equation.
-24 + 8c + -7c = 7c + -7c

Combine like terms: 8c + -7c = 1c
-24 + 1c = 7c + -7c

Combine like terms: 7c + -7c = 0
-24 + 1c = 0

Add '24' to each side of the equation.
-24 + 24 + 1c = 0 + 24

Combine like terms: -24 + 24 = 0
0 + 1c = 0 + 24
1c = 0 + 24

Combine like terms: 0 + 24 = 24
1c = 24

Divide each side by '1'.
c = 24

Simplifying
c = 24

See similar equations:

| 2n+2n=6 | | 14.3u=15.8u+9.6 | | 648-153x+9x^2=0 | | (-5)2+5= | | 14.73-8.6g+8.79=-12.1g-13.93 | | (-C)2+C= | | -3(2z-5y)-z= | | (2y-3)^2/3=(3y)^1/3 | | -14.6v+14.11=-18.5v-14.36 | | 0.3-0.07=x | | (2y-3)^2/3=(3y)^1^3 | | 6h+4h+12=34 | | -20+6b+15b=17b+16 | | -20-11h=-8h+19 | | 10q-55=-5+10q | | 1/9x^2=25 | | 5-f=-11+10f-17 | | 3/4x-12=4-9/4x | | (x-10)+2x+x=3000 | | -2-9q=-7q+10 | | 5(3x+7)-6x=3x+23 | | 141=0+3.3t | | 8(x+3)=8(x+13) | | ln(x)-ln(x-7)=ln(7) | | -9z-8=-z+6-z | | 3x-3=5x+13 | | (-2c-5)-(6c+20)= | | 8/9x-5=27 | | 9+4m=10+5m | | 141=o+3.3t | | (x+10)+2x+x=3000 | | 7x+14=-4x-18 |

Equations solver categories